Breastfeeding education, early skin-to-skin contact and other strong determinants of exclusive breastfeeding in an urban population: a prospective study - Dueñas-Espín, Iván; León Cáceres, Ángela; Álava, Angelica; Ayala, Juan; Figueroa, Karina; Loor, Vanesa; Loor, Wilmer; Menéndez, Mónica; Menéndez, David; Moreira, Eddy; Segovia, René; Vinces, Johanna (BMJ open, 2021)
Objective The current study aims to demonstrate independent associations between social, educational and health practice interventions as determinants of exclusive breastfeeding in an urban Ecuadorian population. - Design Prospective survival analyses. - Setting Ecuadorian mother-child dyads in urban settings. - Participants We followed-up 363 mother-baby dyads who attended healthcare centres in Portoviejo, province of Manabi, for a median time (P25-P75) of 125 days (121-130 days). - Main outcome measures We performed a survival analysis, by setting the time-to-abandonment of exclusive breastfeeding measured in days of life, that is, duration of exclusive breastfeeding, periodically assessed by phone, as the primary outcome. Crude and adjusted mixed-effects Cox proportional hazards model were performed to estimate HRs for each explanatory variable. - Results The incidence rate of abandonment of breastfeeding was 8.9 per 1000 person-days in the whole sample. Multivariate analysis indicated the three most significant protective determinants of exclusive breastfeeding were (a) sessions of prenatal breastfeeding education with an HR of 0.7 (95% CI: 0.5 to 0.9) per each extra session, (b) self-perception of milk production, with an HR of 0.4 (95% CI: 0.3 to 0.6) per each increase in the perceived quantity of milk production and (c) receiving early skin-to-skin contact with an HR of 0.1 (95% CI: <0.1 to 0.3) compared with those not receiving such contact, immediately after birth. - Conclusions Prenatal education on breastfeeding, self-perception of sufficient breast-milk production and early skin-to-skin contact appear to be strong protectors of exclusive breastfeeding among urban Ecuadorian mother-baby dyads.
Gesehen am 07.05.2021